Application of modern analytical techniques and chemometric methods to the chemical characterisation of South African wines : determination of non-volatiles - De Villiers, A. J. (Andre Joubert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2004.